VD_FINDINFO AP / 2011 / 56 vom 25. Februar 2011 - VD Tribunal cantonal (2011)
APPRÉCIATION DES PREUVES, INTERDICTION DE L'ARBITRAIRE | 444 al. 1 ch. 3 CPC, 457 CPC, 465 al. 1 CPC, 471 al. 3 CPC, 9 Cst.